Characterization of Alpine highland pastures located at different altitudes: forage evaluation, chemical composition, in vitro digestibility, fatty acid, and terpene contents. (2nd January 2017) - Peiretti, P. G.; Gai, F.; Alonzi, S.; Battelli, G.; Tassone, S.
Abstract : A survey was conducted over the summer of 2013 on two alpine pastures (P1 and P5), and three mountain pastures (P2, P3, and P4). The aim was to determine the botanical composition, pastoral value (PV), variation in chemical composition, gross energy, in vitro true digestibility (IVTD), in vitro indigestible neutral detergent fiber, fatty acid (FA), and terpene contents of pastures located at different altitudes. PV is highest in alpine pastures (25.7 and 26.9, for P1 and P5, respectively). Exploitation of pastures is intensive only for P1 and P2. Pastures differ in dry matter (DM), ash, crude protein, lipid, and gross energy content. Lignin content was significantly higher in P3 (125 g/kg DM), while in other pastures the variation in its average content (from 73 to 94 g/kg DM) was limited. All pastures had IVTD higher than 725 g/kg with the exception of P3 (659 g/kg). As far as FA content is concerned, in all pastures the most abundant were α-linolenic acid (from 495 to 583 g/kg of total FA) and linoleic acid (from 150 to 222 g/kg of total FA), while palmitic acid and oleic acid significantly differ among pastures. α-Pinene, β-pinene, and p -cymene were the most abundant terpenoids.